2002
DOI: 10.1088/0264-9381/20/1/302
|View full text |Cite
|
Sign up to set email alerts
|

Spacetime structure of the global vortex

Abstract: We analyse the spacetime structure of the global vortex and its maximal analytic extension in an arbitrary number of spacetime dimensions. We find that the vortex compactifies space on the scale of the Hubble expansion of its worldvolume, in a manner reminiscent of that of the domain wall. We calculate the effective volume of this compactification and remark on its relevance to hierarchy resolution with extra dimensions. We also consider strongly gravitating vortices and derive bounds on the existence of a glo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 37 publications
1
29
0
Order By: Relevance
“…A debate on this issue is still ongoing. For a partial list of references on the (still open) issue of the stability of the global monopole, see: [33]; In the original suggestion of Goldhaber that global monopoles are not stable against "angular" collapse, there is an ongoing debate on this issue; for a partial list of references see: [34][35][36][37][38][39][40][41][42]. 5 The motivation for using the above matching comes from the observation that, at the origin (r → 0), the Higgs potential for the scalars leads to a cosmological constant ∝ η 4 , since any "matter" scalar fields…”
Section: Global Monopolesmentioning
confidence: 99%
“…A debate on this issue is still ongoing. For a partial list of references on the (still open) issue of the stability of the global monopole, see: [33]; In the original suggestion of Goldhaber that global monopoles are not stable against "angular" collapse, there is an ongoing debate on this issue; for a partial list of references see: [34][35][36][37][38][39][40][41][42]. 5 The motivation for using the above matching comes from the observation that, at the origin (r → 0), the Higgs potential for the scalars leads to a cosmological constant ∝ η 4 , since any "matter" scalar fields…”
Section: Global Monopolesmentioning
confidence: 99%
“…The obtained unique brane world from a vacuum solution is identified with that of AdS branch in ref. [7,18]. It is also confirmed that any black p-brane structure cannot be formed with a horizon at a finite radius.…”
Section: Introductionmentioning
confidence: 61%
“…Comparison between the two metrics (2.2) and (2.15) provides 18) where x = cosh(ωr − γ). If we rewrite eq.…”
Section: Jhep06(2004)052mentioning
confidence: 99%
“…One finds objects analogous to these topological defects in condensed matter systems (where there is no gravity) for example in flux tubes in type-II superconductors [16], or vortex filaments in a superfluid [17]. Interesting discussions of cosmic strings in brane world scenario can be found in refs [18,19,20] It is important to remark that KR fields have already been introduced in the cosmic string context with dilaton gravity [21,22] and in global vortex with extra dimensions [23]. They are an important ingredient to described vortex configuration in condensed matter systems [24,25,16,17].…”
Section: Jhep03(2005)039mentioning
confidence: 99%